El principio de inmediatez en la acción de tutela contra providencias judiciales (2016)
The Act of Tutela against the Judicial Ruling (TCPJ from the Spanish) it has been seen as an icy topic of constitutional debate in the measurement that has been a source of critiques in relaion to the part of the judicial operators who see without legalized regard the value of their own decisions. Nevertheless, this mechanism of defense is also observed as a weapon against the judicial arbitrariness. This article is limited itself principle of immediateness in the action of tutelage against judicial providence, through the jurisprudence of the maximum court. Similarly formed will announce the legal treatment of the various foreign laws which have given the term of filing of the protection against judicial decisions and the possibilities offered by the discipline of Constitutional Litigation as a peacemaker tool for the lack of action of immediacy principle.